THE EFFECTIVENESS OF POTASSIUM METAVANADATE AS A LOW-CARBON STEEL CORROSION INHIBITOR IN CHLORIDE - CARBONATE - AND SULFIDE - CONTAMINATED ENVIRONMENTS - Farhan Arif, Aditya
Inhibitor addition is one of the common corrosion control methods. Potassium metavanadate (KVO3) is commonly used as corrosion inhibitor in CO2 absorber unit. Chloride and sulfide are common fluids in industry, and are also corrosive. The objective of this research is to study the effectiveness of potassium metavanadate as a lowcarbon steel corrosion inhibitor in the chloride, carbonate, or sulfide - contaminated environments. This objective was achieved by measuring low-carbon steel corrosion rate in different concentrations of contaminants. The corrosion rate was measured by Tafel method. The corrosion inhibition mechanisms were studied using cyclic voltammetry method. Meanwhile the corrosion products were identified by X - ray diffraction spectrometry (XRD). This research results that KVO3 is an effective corrosion inhibitor in chloride environment when the chloride concentration ranges between 20 g/L and 30 g/L. In this range of concentration, KVO3 performs more than 99% efficiency. In sulfide environment KVO3 is an ineffective corrosion inhibitor. While in carbonate environment whose concentration is below 150 g/L, the addition of KVO3 gives no effect to the corrosion reaction. When carbonate concentration is above 150 g/L, it works as an ineffective corrosion inhibitor.